A rare case of perivascular epithelioid cell tumor (PEComa) of the pancreas diagnosed by endoscopic ultrasound - Ulrich, J. D.; Specht, K.; Schlitter, A. M.; Ceyhan, G. O.; Quante, M.; Schmid, R. M.; Schlag, C. (Endoscopy International Open, 2020)
A 49-year-old woman consulted her general practitioner (GP) regarding epigastric pain that she had experienced for 2 months. Physical examination and laboratory results were unremarkable. An abdominal ultrasound indicated a solid pancreatic tumor, which was confirmed on subsequent CT and MRI. Endoscopic ultrasound (EUS) showed a well-defined heterogeneous, predominantly hypoechoic mass in the pancreatic body, so a neuroendocrine tumor (NET) was suspected. However, EUS-guided fine-needle aspiration (EUS-FNA) was performed and based on (immuno-)histochemical findings, the extremely rare diagnosis of a perivascular epithelioid cell tumor (PEComa) of the pancreas was made. Due to the malignant potential of pancreatic PEComas, laparoscopic left-sided pancreatectomy was performed. We present a case diagnosed by preoperative EUS-FNA highlighting the clinical and endosonographic features which help to distinguish it from its most important differential diagnosis, neuroendocrine tumors (NETs) of the pancreas.